Democratisation and the British Empire - Owen, N (Taylor and Francis, 2019)
This article responds to the statistically established finding in democratisation studies that British rule seems to have been good for the survival of democracy in its former empire, and that the longer a nation spent under British rule, the likelier it is to have sustained democracy since independence. This is a finding which puzzles political scientists because they think of democracy and empire as opposites. The article considers the uses made of democratic innovation by the British and the responses anti-colonial nationalists made to the offer to ‘lead them to democracy’. It places democracy and empire in a different, more complex relationship. It also considers the contribution of anti-colonial protest to the working of democracy.